Analisis Representasi Kandidat Perempuan Di Pemilu Legislatif Kabupaten Karawang Periode 2024-2029 - Fatharani, Andini; Hakim, Lukmanul; Mahendra Putri, Lolita Deby (Universitas Pahlawan Tuanku Tambusai, 2025)
The gender affirmative policy mandating a minimum 30% quota for female legislative candidates has not significantly improved women’s political representation in the Karawang Regency DPRD in the 2024 election. This decline reflects structural barriers and entrenched patriarchal culture that limit substantive female political participation. This study analyzes women’s political representation using Hanna Pitkin’s (1967) theory across formal, substantive, symbolic, and descriptive dimensions to evaluate the effectiveness of gender affirmation and identify inhibiting factors. Employing a qualitative phenomenological approach, the research explores women’s experiences and meanings in political representation. Findings reveal that women’s representation is limited to procedural formalities without substantive political commitment from parties, resulting in symbolic representation lacking genuine legitimacy. Patriarchal norms and financially-driven pragmatic politics reinforce women’s subordinate status, hindering their role as effective political agents. The study highlights the necessity for structural and cultural reforms to foster meaningful and empowered women’s representation in local politics. Keywords: Women’s Political Representation, Women’s Representation, DPRD Karawang Regency.